DIMENSI I’JAr Dalam Surah Asy-Syu’ara - Nasrullah; Haq, Ziyadul; Ariyadi, Syamsul (LP2M IAIM Sinjai, 2025)
This research aims to explore the dimension of i'jaz lughawi (linguistic miracle) in the repetition of Quranic verses through the analysis of Tafsir Al-Munir. The primary focus of this study is on Surah Asy-Syuara, Surah Ar-Rahman, and Surah Al-Mursalat. The research method employed is qualitative analysis with a thematic exegesis approach, where Tafsir Al-Munir serves as the main source for understanding the meaning and implications of verse repetition in these three surahs. The findings indicate that the repetition of verses in the Quran not only functions as a rhetorical device but also serves to emphasize important messages, strengthen the reader's memory, and highlight specific aspects of Islamic teachings. In Surah Asy-Syuara, repetition serves to affirm the steadfastness of the prophets and their communities in facing challenges. Surah Ar-Rahman highlights Allah's mercy through the repetition of the phrase